Technology Integration and Internet Connectivity Challenges in the Learning Process: A Literature Review - Syinta M; Nurul Imam; Rosdiana (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
The integration of technology in education has become essential in the digital era, yet its implementation in Indonesia still faces significant challenges. This study aims to analyze technological barriers and their impact on the learning process through library research, reviewing journals, educational reports, and relevant studies. The findings show that technology can enhance flexibility and learning quality, but major obstacles arise from limited infrastructure, insufficient devices, high internet costs, and low digital literacy among teachers and students. The digital divide is especially evident in remote 3T regions with inadequate network access, affecting learning equity and student motivation. Furthermore, the limited readiness of educators and institutional resistance to innovation reduce the effectiveness of digital learning. This study emphasizes that successful digital transformation in education requires comprehensive support, including improved teacher competence, equitable access to infrastructure, and adaptive policies to ensure an inclusive and sustainable implementation.